Effectiveness of group psychotherapeutic practice with orphan patients and patients with external defects - Токарчук, Анастасія (Psychosomatic Medicine and General Practice, 2025)
Introduction. Modern medical and psychological practice shows an increase in the number of patients with rare (orphan) and chronic diseases, accompanied not only by physical limitations, but also by significant psychological difficulties. Systemic psychotherapeutic support for such patients remains underdeveloped, especially in the context of group work. The study highlights the issue of the psychoemotional state of this category of patients and proves the need to integrate group psychotherapy into a comprehensive care system. Methods. The study used qualitative methods of analysis: clinical observation, analysis of cases from group therapy practice, interpretation of psychodynamic processes in a small group. The participants of the therapeutic work were patients with orphan and chronic diagnoses who underwent outpatient treatment. Psychotherapeutic work was carried out in the format of closed groups with a focus on support, expression of emotions and improvement of the internal image of oneself. Results. During the group work, a gradual decrease in the level of anxiety, an increase in self-esteem, an increase in openness and the ability to make emotional contact were observed. Participants acquired self-reflection skills, better understood the mechanisms of their own experiences and behavioral reactions. The group became a source of support, normalized experiences, and increased the sense of belonging to the community, which is especially valuable for patients isolated due to illness. Discussion. The authors emphasize the need to combine psychotherapeutic sensitivity to medical limitations with the flexibility of psychotherapeutic tools. The presence of a diagnosis should not reduce the patient only to a medical object - psychotherapy should consider the personality in its entirety. At the same time, it is emphasized that group work with such patients requires thorough preparation, support from medical specialists, and consideration of the psychophysical resources of each participant. Conclusion. Group psychotherapy is an effective means of support for patients with orphan and chronic diseases. It contributes to improving the quality of life, psychological stabilization, and social reintegration. Successful implementation of such programs is possible only under the condition of multidisciplinary cooperation, clinical awareness of the psychotherapist and adherence to the principle of unconditional acceptance of the participant as an individual. Keywords: facial defects, group psychotherapy, external defects, orphan patients, psychotherapeutic practice.